Fusarium Crown and Root Rot of Tomato in Florida: PP52/PG082, rev. 12/2021 - Zhang, Shouan; Roberts, Pamela D.; Meru, Geoffrey; McGovern, Robert J.; Datnoff, Lawrence E. (EDIS, 2021)
Update of the 2015 version with Geoffrey Meru includes new integrated management procedures to reduce the impact of crown and root rot.